Hubungan Dukungan Keluarga terhadap Kepatuhan Pengobatan Pasien HIV AIDS di UPTD Puskesmas Cilamaya - Indah Yuliani; Ela Nurhayati (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT HIV (Human Immunodeficiency Virus) is a health problem that requires serious attention. HIV is a virus that attacks the human immune system, thus disrupting the body's ability to fight various diseases. This virus infects white blood cells, resulting in decreased immunity, making individuals more susceptible to opportunistic infections and can develop AIDS (Acquired Immune Deficiency Syndrome). Research Objective: To determine the relationship between family support and adherence to HIV/AIDS treatment in Cilamaya Community Health Center. Research Method: Data analysis was conducted using univariate and bivariate methods using chi-square tests. Then, the data was processed using SPSS. Research Results: Of the 42 respondents who were most compliant with HIV/AIDS treatment, 29 respondents (33.8%) were those with good family support. Furthermore, of the 44 respondents who were most non-compliant with TB treatment, 43 respondents (51.1%) were those with poor family support. Conclusion: Based on the chi-square statistical test results, the p-value of this study was 0.020 0.05. H0 was rejected and Ha was accepted, indicating a relationship between family support and treatment adherence in HIV/AIDS patients at the Cilamaya Community Health Center. Keywords: HIV, AIDS, Family Support, Treatment Adherence.  ABSTRAK Penyakit HIV (Human Immunodeficiency Virus) merupakan masalah kesehatan yang memerlukan perhatian serius. HIV adalah virus yang menyerang sistem kekebalan tubuh manusia, sehingga mengganggu kemampuan tubuh untuk melawan berbagai penyakit Virus ini menginfeksi sel darah putih, yang mengakibatkan penurunan daya tahan tubuh, sehingga individu lebih rentan terhadap infeksi oportunistik dan dapat mengembangkan AIDS (Acquired Immune Deficiency Syndrome). Tujuan Penelitian: Diketahuinya Hubungan Dukungan Keluarga Terhadap Kepatuhan Pengobatan Pasien HIV AIDS Di Puskesmas Cilamaya. Metode penelitian: Analisa data dilakukan secara univariat dan bivariat dengan uji chi squre. Kemudian data akan di kelola dengan SPSS. Hasil Penelitian: dari 42 responden yang patuh dalam pengobatan HIV AIDS terbanyak pada responden dengan dukungan keluarga yang baik yaitu sebanyak 33,8%, kemudian yang tidak patuh dalam pengobatan HIV terbanyak pada responden dengan dukungan keluarga yang kurang yaitu sebanyak 51,1%. Penelitian ini dapat disimpulkan bahwa ada Hubungan Dukungan Keluarga Terhadap Kepatuhan Pengobatan Pasien HIV AIDS Di Puskesmas Cilamaya. Kata Kunci: HIV, AIDS, Dukungan Keluarga, Kepatuhan Pengobatan.